Newer Root Canal Irrigants in Horizon: A Review - Sushma Jaju; Prashant P. Jaju (International Journal of Dentistry)
Sodium hypochloride is the most commonly used endodontic irrigant, despite limitations. None of the presently available root canal irrigants satisfy the requirements of ideal root canal irrigant. Newer root canal irrigants are studied for potential replacement of sodium hypochloride. This article reviews the potential irrigants with their advantages and limitations with their future in endodontic irrigation.